The Canvas and the Maze: Deconstructing Wall and Frontier in Contemporary American Science Fiction - Grilli, Chiara (Review of International American Studies, 2018)
Chiara Grilli Independent scholar Italy The Canvas and the Maze: Deconstructing Wall and Frontier in Contemporary American Science Fiction Abstract: Science Fiction has always been used to analyze society through the construction of parallel worlds. Likewise, Denis Villeneuve’s movie Arrival (2016) and the TV series Westworld (2016) challenge respectively the evocative symbol of the wall and the old myth of the American frontier, thanks to the fruitful possibilities of representation offered by the Sci-Fi genre. While in Arrival the wall is turned into the first tool of communication between two cultures, in Westworld the myth depicting America as the land of opportunity connects with that of the frontier and the search for new lands, intended here not as outdoor places, but more importantly as inner spaces. Beside their mystifying power, what connects these two works is a more complex concept of time and of identity: thanks to the screen and the maze, and, as a consequence, thanks to interrelation and introspection, the self is allowed to wander through time, through visionary predictions of the future and hallucinatory mirages of the past, which give the individual the chance to re-build his/her own life story. Keywords: Science Fiction, Wall, American frontier